Genome-wide retroviral insertional tagging of genes involved in cancer in Cdkn2a-deficient mice - Lund, Anders H.; Turner, Geoffrey; Trubetskoy, Alla; Verhoeven, Els; Wientjens, Ellen; Hulsman, Danielle; Russell, Robert; DePinho, Ronald A.; Lenz, Jack; van Lohuizen, Maarten (Nature genetics, 2002)
We have used large-scale insertional mutagenesis to identify functional landmarks relevant to cancer in the recently completed mouse genome sequence. We infected Cdkn2a −/− mice with Moloney murine leukemia virus (MoMuLV) to screen for loci that can participate in tumorigenesis in collaboration with loss of the Cdkn2a -encoded tumor suppressors p16INK4a and p19ARF. Insertional mutagenesis by the latent retrovirus was synergistic with loss of Cdkn2a expression, as indicated by a marked acceleration in the development of both myeloid and lymphoid tumors. We isolated 747 unique sequences flanking retroviral integration sites and mapped them against the mouse genome sequence databases from Celera and Ensembl. In addition to 17 insertions targeting gene loci known to be cancer-related, we identified a total of 37 new common insertion sites (CISs), of which 8 encode components of signaling pathways that are involved in cancer. The effectiveness of large-scale insertional mutagenesis in a sensitized genetic background is demonstrated by the preference for activation of MAP kinase signaling, collaborating with Cdkn2a loss in generating the lymphoid and myeloid tumors. Collectively, our results show that large-scale retroviral insertional mutagenesis in genetically predisposed mice is useful both as a system for identifying genes underlying cancer and as a genetic framework for the assignment of such genes to specific oncogenic pathways.